Giant deep orbital dermoid cyst presenting early in infancy in a Nigerian child: a case report and review of the literature - Fasina, Oluyemi (BioMed Central, 2012)
INTRODUCTION: Dermoid cysts are the most common orbital cystic lesions seen in children. While superficial orbital dermoid cysts present early in life, deep dermoid cysts remain clinically occult until adolescence or adulthood. We here present a case of a deep orbital dermoid cyst in a Nigerian child that became symptomatic early in infancy. CASE PRESENTATION: A female Nigerian infant of Yoruba ethnicity presented at three months of age with left non-axial proptosis and a hazy cornea. A superotemporal cystic orbital mass was seen on ultrasonography, and her parents were counseled for simple tumor excision. They however defaulted, only for their child to re-present two years later with gradually progressive proptosis, an enlarged orbit and keratinized ocular surface, necessitating orbital exenteration. CONCLUSION: Deep orbital dermoid cysts may be symptomatic from birth. Late presentation may result in an irreversible loss of vision, as demonstrated in our case. The need for public enlightenment on early presentation and prompt management of such benign lesions is emphasized.